UTILIZATION OF MAN‐MADE ROOSTS BY TURKEY IN WEST TEXAS - H. G. Kothmann; G. W. Litton (Wildlife Society Bulletin)
Abstract The Rio Grande turkey (Meleagris gallopavo intermedia) has extended its range into 1.4 million hectares (ha) of semiarid scrub mesquite prairie in West Texas. A well established and increasing population exists where the southern edge of the High Plains meets the Edwards Plateau and Trans‐Pecos. Population fluctuations are proportional to range conditions and rainfall patterns. Natural roost sites are absent, but man‐made structures such as utility lines and poles, oil storage tanks, and windmill towers provide adequate substitutes.